Prevalence of antibodies to hepatitis B, hepatitis C, and HIV and risk factors in Irish prisoners: results of a national cross sectional survey. Issue 7253 (8th July 2000) - Allwright, Shane; Bradley, Fiona; Long, Jean; Barry, Joseph; Thornton, Lelia; Parry, John V
Abstract: Objectives: To determine the prevalence of antibodies to hepatitis B core antigen, hepatitis C virus, and HIV in the prison population of the Republic of Ireland and to examine risk factors for infection. Design: Cross sectional, anonymous, unlinked survey, with self completed risk factor questionnaire and provision of oral fluid specimen for antibody testing. Setting: Nine of the 15 prisons in the Republic of Ireland. Participants: 1366 prisoners, of whom 1205 (57 women) participated. In the smaller prisons all prisoners were surveyed, while in the three largest prisons one half of the population was randomly sampled. Three small prisons believed not to have a problem with injecting drug use were excluded. Main outcome measures: Prevalence of antibodies to hepatitis B core antigen, antibodies to hepatitis C virus, and antibodies to HIV. Self reported risk factor status. Results: Prevalence of antibodies to hepatitis B core antigen was 104/1193 (8.7%; 95% confidence interval 7.2% to 10.5%), to hepatitis C virus, 442/1193 (37%; 34.3% to 39.9%), and to HIV, 24/1193 (2%; 1.3% to 3%). The most important predictor of being positive for hepatitis B and hepatitis C was a history of injecting drug use. Thirty four women (60%) and 474 men (42%) reported ever injecting drugs. A fifth (104) of 501 injecting drug users reported first injecting in prison, and 347 (71%) users reported sharing needles in prison. Conclusions: Infection with hepatitis C secondary to use of injected drugs is endemic in Irish prisons. Better access to harm reduction strategies is needed in this environment.